THE INFLUENCE OF UNDERSTANDING THE VALUES OF THE QUR'AN, SURAT AL-ISRA VERSE 7 ON STUDENTS' LEARNING DISCIPLINE - Achmad Faqih; Dindin Saefudin; Moch. Hilman Taabudilah (Al - Mujaddid: Jurnal Ilmu-ilmu Agama, 2025)
This study aims to analyze the influence of understanding the values of Al-Qur'an Surah Al-Isra verse 7 on the learning discipline of students in class XII-TKJ 2 at SMK Negeri Situraja. Field phenomena show that there are still students who lack discipline in learning, such as being late to class, neglecting assignments, and lacking focus in following lessons due to excessive use of gadgets. This condition reflects a weak awareness of discipline that should go hand in hand with Islamic values, one of which is contained in QS. Al-Isra verse 7 which teaches the principle of personal responsibility that every good deed will return to the doer as goodness and every bad deed will return as badness. This study uses a quantitative approach with an associative research type. The research population consisted of 36 students who were also used as samples using saturated sampling technique. Data were collected through observation, documentation, and questionnaire distribution with Likert scale measuring five indicators of understanding Quranic values namely personal responsibility, goodness repays goodness, justice of Allah, self-introspection, and moral independence, then analyzed using simple linear regression test, t-test, and coefficient of determination with the help of SPSS version 25 program. Research instruments have been tested for validity and reliability. The results showed that understanding of QS. Al-Isra verse 7 was in the good category with a percentage of 81 percent, likewise students' learning discipline also reached the good category with a percentage of 81 percent. Based on the results of simple linear regression analysis with the equation Y = 31.154 + 0.236X, it was found that there was a positive and significant influence between understanding QS. Al-Isra verse 7 and learning discipline with Pearson correlation coefficient value of 0.430 indicating a moderate level of relationship closeness and coefficient of determination of 18.5 percent. Hypothesis test results show t count value 2.776 is greater than t table 1.690 with a significance value of 0.009 which is smaller than 0.05. Thus it can be concluded that the higher students' understanding of the values contained in QS. Al-Isra verse 7, the higher the level of learning discipline shown, this proves that the internalization of Quranic values especially regarding personal responsibility and the law of cause and effect can become a strong spiritual foundation in forming students' disciplined character.